2020
DOI: 10.3390/md18030172
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Ultrasound, Microwave and Ultrasound–Microwave Assisted Extraction Technologies to Increase the Extraction of Bioactive Compounds and Antioxidants from Brown Macroalgae

Abstract: This study aims to determine the influence of (1) ultrasound-assisted extraction (UAE), (2) microwave-assisted extraction (MAE) and (3) a combination of ultrasound–microwave-assisted extraction (UMAE) on the yields of fucose-sulphated polysaccharides (FSPs), total soluble carbohydrates and antioxidants extracted from A. nodosum. Scanning electron microscopy (SEM) was used to evaluate the influence of the extraction technologies on the surface of macroalgae while principal component analysis was used to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(73 citation statements)
references
References 41 publications
2
70
0
1
Order By: Relevance
“…The cell surfaces of treated samples exhibit an increased porosity that facilitated the extraction of higher yields of TPC and TPhC compared to control samples (Table 1). Previously, Rodriguez-Jasso et al [22] and Garcia-Vaquero et al [23] reported similar findings when evaluating the efficiency of MAE, UAE and UMAE (ultrasound-microwave assisted extraction) to generate extracts from F. vesiculosus and A. nodosum seaweed.…”
Section: Scanning Electron Microscopic Analysismentioning
confidence: 58%
See 1 more Smart Citation
“…The cell surfaces of treated samples exhibit an increased porosity that facilitated the extraction of higher yields of TPC and TPhC compared to control samples (Table 1). Previously, Rodriguez-Jasso et al [22] and Garcia-Vaquero et al [23] reported similar findings when evaluating the efficiency of MAE, UAE and UMAE (ultrasound-microwave assisted extraction) to generate extracts from F. vesiculosus and A. nodosum seaweed.…”
Section: Scanning Electron Microscopic Analysismentioning
confidence: 58%
“…Scanning Electron Microscopy (SEM) was used to investigate the effect of ultrasound on F. vesiculosus surface characteristics. Dried seaweed samples and pellets from the extraction conditions achieving high extraction yields (35 kHz, 50% ethanol, 30 min) and control (no ultrasound, 50% ethanol, 30 min) were collected and prepared as described by Garcia-Vaquero et al [23]. The images were recorded using a SEM Regulus 8230 (Hitachi Ltd., Tokyo, Japan).…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…Worth mentioning, among them are phytopigments (xanthophylls and carotenoids), polyunsaturated fatty acids (PUFAs) comprising docosahexaenoic acid (DHA), phenolic compounds, tannins, peptides, lipids, enzymes, vitamins, carbohydrates, terpenoids, and others. Thus, algae are a viable and economical biomass source of valuable compounds with potential applications in the nutraceutical, pharmaceutical, chemical, food, and cosmetic industries due to their biologically active and regenerative properties [ 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…10 Recently, accelerated and compressed uid-based extraction techniques such as Accelerated Solvent Extraction (ASE), Ultrasound-Microwave Assisted Extraction (UMAE), Pressurized Liquid Extraction (PLE) and Supercritical Antisolvent Fractionation (SAF), have gained considerable interest in the extraction of bioactive substances from algae. [11][12][13] Many of these techniques are efficient on a small scale, not being widely applied in the industrial eld due to their high energy requirements. 14 In addition, there is currently a limited understanding of the key variables that affect the performance of these extraction processes.…”
Section: Introductionmentioning
confidence: 99%